ความสัมพันธ์ระหว่างอัตราดอกเบี้ยที่แท้จริงกับอัตราแลกเปลี่ยนของไทย มาเลเซีย สิงคโปร์ อินโดนีเซีย และฟิลิปปินส์ - พันโท มะรินทร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The objective of this study is Relationship Between Real Interest Rates and Exchange Rates of Thailand, Malaysia, Singapore, Indonesia and The Philippines. Secondary annual data on real interest rates and exchange rates during 1996-2010 period of five ASEAN countries. For the analysis. The test for unit roots of the panel data indicates all sets of variable are stationary and co-integrated at I(1) level. The test of panel equation reveals that the relationshipbetween realinterest rates and exchange rates. The panel data were used for various model estimations and it was found that the optimal form for the present study was the fixed effects model. The model estimation by Ordinary Least Squares method provides the result that real interest rates is negatively related with the exchange rates in Thailand, Malaysia, Singapore, Indonesia and The Philippines. The increase in real interest rates led to the reduced exchange rates. For this reason, The reduce in real interest rates make increase exchange rates. The intercept term of the fixed effects model can be interpreted as the combined impact from external factors which falls on every ASEAN country under study.